Impact of the Dissolution of the Soviet Union on the Emergence of Authoritarian Regimes in Central Asia - Kyarizova, Sofia (2024)
The disintegration of the Soviet Union in 1991 marked a defining moment in the histories of the former republics, transforming the decisive political trajectories in Central Asia. The formal bureaucratic mechanisms of the apparatus deteriorated, which the ruling elites have exploited in order to exert control over the economic resources and political power.The objective of the policy was the destruction of the Soviet Union through political and legal mechanisms. The economic stagnation was marked by the substantial decline in productivity, innovation and technological deficiency. The centralized government apparatus, once a fundamental building block of the Soviet economic power, transformed into an inefficient apparatus oblivious to the needs of the plights of the economy. All in all, the disintegration of the Soviet Union instigated an environment where ubiquitous corruption penetrated and facilitated the emergence of the nomenclatura elites within each newly independent state.